2020
DOI: 10.1515/hc-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative coupling between benzaldehyde derivatives and phenylacetylene catalyzed by rhodium complexes via C-H bond activation

Abstract: This paper reports the use of rhodium (Rh) catalysts for the oxidative coupling reaction between phenylacetylene and benzaldehyde derivatives via C-H bond activation. These reactions were catalyzed by Rh(l-amino acid)(cod) (the l-amino acid is l-phenylalanine, l-valine or l-proline; cod is 1,5-cyclooctadiene) to obtain chromones in 12.7-88.3% yield. These new Rh catalysts have excellent activity for the coupling reaction between phenylacetylene and different benzaldehyde derivatives. It was found that the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For instance, L-phenylalanine, L-valine, and Lproline were introduced as anionic ligands in Rh-COD compounds to give chiral complexes for the oxidative coupling reaction between phenylacetylene and benzaldehyde derivatives, producing seven types of chromones via C-H bond activation. Yields were variable, comprised between about 13-88%, depending on the electronic nature of the substituents on the benzaldehyde derivatives [80]. Moreover, it was found that when the amino acid was L-phenylalanine with its large aromatic moiety, it could easily dissociate from the metal centre to leave an empty active site, thus increasing the catalytic activity of the Rh complex.…”
Section: Miscellaneousmentioning
confidence: 99%
“…For instance, L-phenylalanine, L-valine, and Lproline were introduced as anionic ligands in Rh-COD compounds to give chiral complexes for the oxidative coupling reaction between phenylacetylene and benzaldehyde derivatives, producing seven types of chromones via C-H bond activation. Yields were variable, comprised between about 13-88%, depending on the electronic nature of the substituents on the benzaldehyde derivatives [80]. Moreover, it was found that when the amino acid was L-phenylalanine with its large aromatic moiety, it could easily dissociate from the metal centre to leave an empty active site, thus increasing the catalytic activity of the Rh complex.…”
Section: Miscellaneousmentioning
confidence: 99%